2012
DOI: 10.1049/iet-com.2012.0028
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of highly absorbent and highly reflective radio wave propagation environments in industrial applications

Abstract: Experience has shown that Bluetooth, Wireless LAN (WLAN), Digital Enhanced Cordless Telecommunications (DECT) and other Industrial, Scientific and Medical (ISM) frequency band wireless technologies developed for office use, have encountered problems when used in critical industrial applications. The development of more reliable wireless solutions requires extensive knowledge of industrial environments with regards to both electromagnetic interference and wave propagation. This study presents the results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
18
0
3
Order By: Relevance
“…The measurements were conducted along two measurement routes using two access points installed at 2 m and 4.85 m with the receiver being at 1 m above the ground. Measurements spanning over a large frequency band 200-2500 MHz were also carried out in an industrial environment [7] where the transmitter/receiver antennas were mounted 1 m above the floor. The measurements included 1601 measurement points with a maximum distance of 18 m between the transmitter and receiver locations.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were conducted along two measurement routes using two access points installed at 2 m and 4.85 m with the receiver being at 1 m above the ground. Measurements spanning over a large frequency band 200-2500 MHz were also carried out in an industrial environment [7] where the transmitter/receiver antennas were mounted 1 m above the floor. The measurements included 1601 measurement points with a maximum distance of 18 m between the transmitter and receiver locations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as shown in Fig. 1, the stripper-related XMEASs (XMEAS [15][16][17][18][19] share one wireless node at the same spot. However, each PV is allocated its own wireless bandwidth in a periodic manner to guarantee deterministic transmission within the network.…”
Section: B Network Model In the Te Plantmentioning
confidence: 99%
“…Other intermittent interference from nearby wireless nodes can be traced and mitigated through the co-existence solutions provided for example in [21], [22]. Additional information on wireless channel characterizations in the industrial plant environments can be found in [17], [18], [34].…”
Section: B Network Model In the Te Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…Multipath propagation has been studied and characterized in a multitude of environments, such as residential buildings, indoor offices and mines. The work performed in [6] proposes statistical models for estimating the root-mean-square (RMS) delay spread, path-loss and other relevant propagation [10] 1.89 0.5 298 Paper mill [10] 1.89 0.5 23 Subway tunnel [11] 2.4 0.1 159-234 Road tunnel [12] 5.2 0.1 20-100 Mine tunnel [13] 1 0.2 20-50 Mine tunnel [14] 2.4 0.5 14 Mine tunnel [15] 2.4 0.2 27.4 Mine tunnel [16] 2.4/5.8 0.2 1-15 Mine tunnel [17] 3.5 3 11-29 Mine tunnel [18] 2.4 0.2 1.7 LiU tunnel 3.5 2 3-16…”
Section: A Overview Of Measurements Campaignsmentioning
confidence: 99%